Spatial sterol metabolism unveiled by stimulated Raman imaging - Yongqing Zhang; Yihui Zhou; Wen Fang; Hanlin Zhu; Cunqi Ye; Delong Zhang; Hyeon Jeong Lee (Frontiers in Chemistry, 2023)
Spatiotemporal dynamics of small-molecule metabolites have gained increasing attention for their essential roles in deciphering the fundamental machinery of life. However, subcellular-level regulatory mechanisms remain less studied, particularly due to a lack of tools to track small-molecule metabolites. To address this challenge, we developed high-resolution stimulated Raman scattering (SRS) imaging of a genetically engineered model (GEM) to map metabolites in subcellular resolution. As a result, an unexpected regulatory mechanism of a critical metabolite, sterol, was discovered in yeast by amplifying the strength of vibrational imaging by genetic modulation. Specifically, isozymes of 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) were evident to promote ergosterol distribution to distinct subcellular locations, where ergosterol was enriched by a local HMGR-directed synthesis. The heterogeneity of this expression pattern thus provides new insights into sterol metabolism and related disease treatment strategies. These findings demonstrate SRS-GEM as a promising platform for new possibilities in investigating metabolic regulation, disease mechanisms, and biopharmaceutical research.